Gamifikasi sebagai Metode untuk Mendapatkan Customer Loyalty: Review Literatur - Andi Wahju Rahardjo Emanuel; Fedelis Brian Putra Perkasa (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2020)
Customer loyalty is one of the important things in the business area. This is because customer loyalty can provide additional revenue for the business sector. Customer loyalty is applied not only to the retail business, but many other business sectors that implement it. Customer loyalty has several variables and factors that can influence it. These include engagament, satisfaction and brand. These three factors can be generated from the application of gamification. Therefore, in this study we will explain about gamification that can affect customer loyalty. In this study, the elements of the game will be discussed in accordance with this context, how to implement them and what impacts they will produce. The results of this study conclude that there are several gamification elements that can be applied. Also demonstrated the implementation of gamification that is suitable for this problem.